Il Green Pass nella realtà dell’emergenza. Riflessioni a partire dal Parere del Comitato Nazionale per la Bioetica del 30 aprile 2021. - Tarantino, Giovanni (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2023)
If in the common narrative the Green Pass seems to aim at easing the restrictions imposed by the emergency regulations issued to combat the pandemic, its real goal, on the other hand, could be to push people to undergo vaccination against Covid-19. The tool of the Green Pass, however, goes beyond the ordinary medical use already foreseen for some time for other certifications within the National Health Service, thus bringing out numerous problems, in a plurality of areas, on which bioethics is called to reflect.